James McCreet’s Neo-Victorian novels and the critique of Victorian culture - Ababneh, Inas (Research Journal in Advanced Humanities, 2026)
This study explores how contemporary novelist James McCreet revisits Victorian society to challenge dominant historical narratives and give voice to marginalized figures. In his novels, McCreet exposes the marginalization of the physically deformed, the transportees, and the poor. By examining how neo-Victorian fiction reimagines the past, the paper highlights the importance of questioning inherited cultural hierarchies and binary oppositions that continue to shape modern thinking. This paper examines the way James McCreet (b. 1971) writes back to the Victorian center. As a neo-Victorianist, McCreet views the Victorian society as a site for conflicting voices. As such, he brings the marginalized individuals from the Victorian society to the center.